2000
DOI: 10.1126/science.288.5470.1407
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Denitrification and Its Effect on Ozone Recovery

Abstract: Upper Atmosphere Research Satellite observations indicate that extensive denitrification without significant dehydration currently occurs only in the Antarctic during mid to late June. The fact that denitrification occurs in a relatively warm month in the Antarctic raises concern about the likelihood of its occurrence and associated effects on ozone recovery in a colder and possibly more humid future Arctic lower stratosphere. Polar stratospheric cloud lifetimes required for Arctic denitrification to occur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 60 publications
5
133
0
Order By: Relevance
“…Potentially, a denitrified Arctic stratosphere in early spring is primed for ozone destruction because reactive nitrogen that can mediate ozone loss (by sequestering active chlorine) has been removed from the stratosphere. In fact, a number of studies have shown that massive denitrification in the Arctic can increase ozone loss by about 30% in a nonvolcanic stratosphere (17,18), which is in accord with the results shown in Fig. 3.…”
Section: Model Simulationssupporting
confidence: 80%
See 3 more Smart Citations
“…Potentially, a denitrified Arctic stratosphere in early spring is primed for ozone destruction because reactive nitrogen that can mediate ozone loss (by sequestering active chlorine) has been removed from the stratosphere. In fact, a number of studies have shown that massive denitrification in the Arctic can increase ozone loss by about 30% in a nonvolcanic stratosphere (17,18), which is in accord with the results shown in Fig. 3.…”
Section: Model Simulationssupporting
confidence: 80%
“…3 vortex-averaged denitrification fields (Insets) are shown for the winter of 1999-2000 for four cases. As shown (13,17,18), denitrification is enhanced in a colder (by 4 K) nonvolcanic atmosphere. Most of the denitrification in a nonvolcanic atmosphere is caused by sedimentation of large NAD (or NAT) particles (13).…”
Section: Model Simulationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Several CTM studies have shown that denitrification in mid-winter can increase springtime Arctic ozone loss by reducing HNO 3 concentrations in the lower stratosphere, thus reducing the rate of ClO x deactivation and extending the ozone loss period (e.g. Chipperfield and Pyle, 1998;Waibel et al, 1999;Tabazadeh et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%